1993
DOI: 10.2307/3431695
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 2-Aminofluorene by Human Polymorphonuclear Leukocytes: More Evidence for the Association between Inflammation and Cancer

Abstract: Recent investigations have demonstrated the ability of leukocytes to metabolize promutagens or procarcinogens into their genotoxic forms. As a possible explanation for the association between inflammation and cancer, we and others have hypothesized that local accumulations of leukocytes could take up nearby promutagens, metabolize them, and release genotoxic agents that may cause damage in the surrounding tissue. Using a modified, two-step preincubation protocol with Salmonella, we have tested this hypothesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…(18,28) Additionally, metabolism of AF by venous leukocytes generated undetermined metabolites other than N-OH-AF that appeared to be Salmonella typhimurium strain TA98 mutagens. (33) Currently, there are no studies on the prolonged and persistent existence of T cell anomalies and immunosuppression in AF exposed animals or humans, not to mention, few, if any, detailed studies on components of the immune system. However, Beland et al (1999), and Chen et al (2001), have shown the production of AF-associated DNA adducts in rats fed 2-AAF and 2-N-OH-AAF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(18,28) Additionally, metabolism of AF by venous leukocytes generated undetermined metabolites other than N-OH-AF that appeared to be Salmonella typhimurium strain TA98 mutagens. (33) Currently, there are no studies on the prolonged and persistent existence of T cell anomalies and immunosuppression in AF exposed animals or humans, not to mention, few, if any, detailed studies on components of the immune system. However, Beland et al (1999), and Chen et al (2001), have shown the production of AF-associated DNA adducts in rats fed 2-AAF and 2-N-OH-AAF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is abundant in the azurophilic granules of neutrophils, neutrophil precursors and monocyte/macrophages, and is present at the promyelocyte stage of myeloid maturation (Pember and Kinkade 1983; Subrahmanyam et al 1991). Several environmental chemicals are reported to be activated by MPO to genotoxic metabolites (Arlt et al 2006; Isola et al 1993; Kagan et al 2000; Kalf et al 1991; Lakshmi et al 2000; Shen et al 1990), which could be the basis of selective target organ toxicity and carcinogenicity of certain compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It is now associated with numerous diseases, such as cancers (14), infections, wound healing processes (9,10), Alzheimer's disease, etc. In cases of eye diseases, posterior retinal inflammation could lead to posterior retinal pole degenerative lesions which are related to posterior uveitis, high myopia, agerelated macular degeneration and glaucoma (15).…”
Section: Discussionmentioning
confidence: 99%